Awareness of nursing students towards cancer and their comparison with medical students - S., Radhika; A., Najma R.; Bharadwaj, Ira (International Journal of Research in Medical Sciences, 2020)
Background: Cancer is the 2nd leading cause of mortality worldwide. The three leading cancers in India are cervical cancer, breast cancer and upper aerodigestive tract carcinoma. Cervical carcinoma is the 2nd most common cancer in women next to breast carcinoma. This study has been done to assess the knowledge, causation and preventive methods about the common cancers in India amongst Medical and Nursing students in a tertiary care center in rural Kerala. Preventive measures and early diagnosis of cancer can lead to decrease in mortality and morbidity. This can be achieved by creating awareness. A special emphasis has been made regarding cervical cancer and HPV vaccination in this study. Methods: A total of 337 medical and 148 nursing students from 1st year to final year were included in this study and the results were analysed by descriptive statistics. Results: Out of 337 medical and 148 nursing students, there was significant difference in knowledge between pretest/posttest and amongst the medical/nursing students. Medical students were found be more aware about the cancer, their causation and preventive methods as compared to the nursing students. 76.4% of nursing students were aware about the role of HPV (Human Papilloma Virus) in the causation of cervical cancer pretest. 98.6% of nursing students were aware about the role of HPV in causation of cervical cancer posttest following a short lecture. Following a short lecture both medical and nursing students were found to have more awareness. Conclusions: Creating awareness to the medical and nursing students who are intouch with the community and the patients is essential. Targeted health education in very important in creating a great impact about the knowledge of cancer in the community, thereby leading to decrease in mortality and morbidity.